A photoactivatable nanopatterned substrate for analyzing collective cell migration with precisely tuned cell-extracellular matrix ligand interactions - Shimizu, Yoshihisa; Böhm, Heike; Yamaguchi, Kazuo; Spatz, Joachim P.; Nakanishi, Jun (PLOS ONE, 2014)
Collective cell migration is involved in many biological and pathological processes. Various factors have been shown to regulate the decision to migrate collectively or individually, but the impact of cell-extracellular matrix (ECM) interactions is still debated. Here, we developed a method for analyzing collective cell migration by precisely tuning the interactions between cells and ECM ligands.
Gesehen am 23.09.2020